Evaluation of the clinical effectiveness of miniscrews in class I and II malocclusion patients - Ali Amiri; Setareh Khosravi; Abolfazl Habibi Arbastan; Sara Jafarizadeh (Universidade Estadual de Campinas, 2021)
Aim: The present systematic review and meta-analysis aimed to evaluate the clinical effectiveness of miniscrews in Class I and II Malocclusion Patients. Methods: From electronic databases, between 2010 and 2020, PubMed, Embase, Cochrane Library, ISI were used to conduct systematic literature. Two reviewers extracted data blindly and independently from the abstract and full text of the studies they used for data extraction. The mean differences between the two groups (miniscrews vs. conventional anchorage) with a 95 % confidence interval (CI), the Inverse-variance method, and the fixed-effect model were calculated. The Meta-analysis was evaluated using the statistical software Stata/MP v.16 (The fastest version of Stata). Results: A total of 186 potentially relevant titles and abstracts were found during the electronic and manual search. Finally, the inclusion criteria required for this systematic review were met by a total of seven publications. The mean difference of molar mesiodistal movement among seven studies and heterogeneity was -0.53 mm (MD, -0.53 95 % CI -0.69, -0.38. P= 0.00) (I2 = 96.52 %). This result showed maximum reinforcement in miniscrews with fewer mesial movements. Conclusion: The result of the current systematic review and meta-analysis shows that miniscrews in patients with class II and I malocclusion help maintain better anchorage preservation than traditional anchorage devices.